2009
DOI: 10.1177/1069397109336991
|View full text |Cite
|
Sign up to set email alerts
|

Centrality of and Investment in Work and Family Among Israeli High-Tech Workers

Abstract: Workers' attitudes concerning the competition for individual's resources between work and family are expressed by the relative centrality they attribute to each of these domains. This competition is also manifested in the tradeoff between work and family time. The study deals with 319 Israeli high-tech workers. We examined the effect of parenthood on men and on women regarding the centrality of and investment in work and family in the bicultural context of the Israeli high-tech industry (i.e., the family-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 60 publications
6
40
1
3
Order By: Relevance
“…Previous research has shown a link between the occurrence of certain HWI behaviors and national culture (Snir and Harpaz, 2009b;Snir et al, 2009), so future researchers should conduct intercultural studies to test the generalizability of our typology. Also, previous research notes that effects of work investment behaviors may change over time (Killinger, 1991), so future researchers might conduct longitudinal studies that could add a temporal element in the biopsychosocial framework, since.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown a link between the occurrence of certain HWI behaviors and national culture (Snir and Harpaz, 2009b;Snir et al, 2009), so future researchers should conduct intercultural studies to test the generalizability of our typology. Also, previous research notes that effects of work investment behaviors may change over time (Killinger, 1991), so future researchers might conduct longitudinal studies that could add a temporal element in the biopsychosocial framework, since.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has also shown that differences in work investment can be connected to social factors including demographic and cultural differences. For demographics, research finds a counter-intuitive effect of parenthood on women who devote more time to work after becoming parents and men who devote less (Snir et al, 2009). For cultural differences, research finds that work investment is related to cultural values including those of survival and masculinity, both of which are linked to increased work investment (Snir and Harpaz, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Time invested in family was positively related to the number of children at home. In a recent study Snir, Harpaz, and Ben-Baruch (2009) found that a contrasting parenthood effect on men and women prevails even in the demanding high-tech sector, where women are expected to work long hours and play down HWI: heavy investment of both (1) time and (2) effort in work.…”
Section: Background Predictorsmentioning
confidence: 97%
“…Historically, high-tech has been identified as a male-dominated profession (e.g., Griffiths, Moore, & Richardson, 2007;Michie & Nelson, 2006;Snir, Harpaz, & Ben-Baruch 2009;von Hellens, Neilson, & Beekhuyzen, 2004). Extant research has indicated women may shy away from such occupations due to environmental influences such as gendered expectations and gendered image of the profession.…”
Section: High-tech: a Gendered Occupationmentioning
confidence: 99%